Emotion and Mood Adaptations in the Peripartum Female: Complementary Contributions of GABA and Oxytocin. (October 2014) - Lonstein, J. S.; Maguire, J.; Meinlschmidt, G.; Neumann, I. D.
<x xml:space="preserve">Abstract</x> Peripartum hormones and sensory cues from young modify the maternal brain in ways that can render females either at risk for, or resilient to, elevated anxiety and depression. The neurochemical systems underlying these aspects of maternal emotional and mood states include the inhibitory neurotransmitter GABA and the neuropeptide oxytocin (OXT). Data from laboratory rodents indicate that increased activity at the GABAA receptor contributes to the postpartum suppression of anxiety‐related behaviour that is mediated by physical contact with offspring, whereas dysregulation in GABAergic signalling results in deficits in maternal care, as well as anxiety‐ and depression‐like behaviours during the postpartum period. Similarly, activation of the brain OXT system accompanied by increased OXT release within numerous brain sites in response to reproductive stimuli also reduces postpartum anxiety‐ and depression‐like behaviours. Studies of peripartum women are consistent with these findings in rodents. Given the similar consequences of elevated central GABA and OXT activity on maternal anxiety and depression, balanced and partly reciprocal interactions between these two systems may be essential for their effects on maternal emotional and mood states, in addition to other aspects of postpartum behaviour and physiology.